Probing Neuro-Endocrine Interactions Through Remote Magnetothermal Adrenal Stimulation - Maeng, Lisa Y.; Rosenfeld, Dekel; Simandl, Gregory J.; Koehler, Florian; Senko, Alexander W.; Moon, Junsang; Varnavides, Georgios; Murillo, Maria F.; Reimer, Adriano E.; Wald, Aaron; Anikeeva, Polina; Widge, Alik S. (Frontiers in Neuroscience, 2022)
Exposure to stressful or traumatic stimuli may alter hypothalamic-pituitary-adrenal (HPA) axis and sympathoadrenal-medullary (SAM) reactivity. This altered reactivity may be a component or cause of mental illnesses. Dissecting these mechanisms requires tools to reliably probe HPA and SAM function, particularly the adrenal component, with temporal precision. We previously demonstrated magnetic nanoparticle (MNP) technology to remotely trigger adrenal hormone release by activating thermally sensitive ion channels. Here, we applied adrenal magnetothermal stimulation to probe stress-induced HPA axis and SAM changes. MNP and control nanoparticles were injected into the adrenal glands of outbred rats subjected to a tone-shock conditioning/extinction/recall paradigm. We measured MNP-triggered adrenal release before and after conditioning through physiologic (heart rate) and serum (epinephrine, corticosterone) markers. Aversive conditioning altered adrenal function, reducing corticosterone and blunting heart rate increases post-conditioning. MNP-based organ stimulation provides a novel approach to probing the function of SAM, HPA, and other neuro-endocrine axes and could help elucidate changes across stress and disease models.